Retrospective Study of 109 Patients with Scabies: Profile of a Region - Kieselova, Katarina; Santiago, Felicidade; Henrique, Martinha (Journal of the Portuguese Society of Dermatology and Venereology, 2018)
Introduction: Scabies is a common cutaneous infestation occurring at any age and, in some communities, it represents a major public health problem. In Portugal, there is a lack of studies about this parasitosis. The aim of our study was to evaluate the principal characteristics of the patients with scabies diagnosed in Department of Dermatology in Centro Hospitalar de Leiria. Material and Methods: We performed a retrospective observational study, including patients diagnosed with scabies observed at the Consultation and Urgency of General Dermatology and at the Consultation and Urgency of Pediatric Dermatology of CHL between January 2015 and December 2016. Results: The study included 109 patients (69 children; 40 adults). The mean age of the patients in the pediatric group was 6.95 years (± 5.92) and 47.33 years (± 22.06) in the group of adults. In 2015, we diagnosed 46 cases of scabies and in 2016, 63 cases were diagnosed, which represents an increment of 37%. The majority of patients (74.3%) was not able to identify the source of contagion. The diagnostic delay was similar in both groups (50 days in the pediatric vs 58 days in the adult group), nonetheless the diagnostic concordance was much higher in the pediatric group (70.8% vs 27.6%, p = 0.000). Conclusion: The authors present the first study of patients affected by scabies in Portugal, showing an increasing incidence, yet probably underestimated. Similarly, other studies have shown that the diagnostic delay is still relevant both in adults and children, however, we highlight higher diagnostic concordance in the pediatric group. The knowledge of the local epidemiologic features of scabies permits to design more consistent preventive strategies and social support.